Flexible Electronics: Mechanically Tunable Magnetic Properties of Flexible SrRuO3 Epitaxial Thin Films on Mica Substrates (Adv. Electron. Mater. 4/2018). (16th April 2018) - Liu, Jindong; Feng, Yu; Tang, Rujun; Zhao, Run; Gao, Ju; Shi, Daning; Yang, Hao
Abstract : In the article number1700522, Jindong Liu, Hao Yang, and co‐workers report on the mechanically tunable magnetic properties of flexible SrRuO3 epitaxial thin films on mica substrates. Applying a compressive mechanical strain enhances the saturated magnetic moment by more than 260%. The films exhibit highly tunable magnetic properties and hold a great potential for applications in memory, sensors, flexible electronics, and spintronics devices.